Efficiency of treatment of the tuberculosis in children of early age - А. V. Моrdyk; М. А. Plekhanova; Yе. А. Tsygankova (Бюллетень сибирской медицины)
For the purpose of a comparative estimation of efficiency treatment of a tuberculosis in children of early age, 272 cases for two ten years' periods (2001—2010, 1985—1994) were analyzed. In connection with negative shifts in an epidemiological picture of a tuberculosis last decade (growth of widespread forms of a tuberculosis is more often, at a source of infection were registered the bacterioexcretion and drug resistance), at tuberculosis treatment has increased medicinal loading on an organism of the child that promoted development of collateral reactions to antitubercular preparations and less often it was possible to reach full resolution of specific changes.